Taxa de aplicação e uso de surfactante siliconado na deposição da pulverização e controle da ferrugem da soja - Prado, Evandro P. [UNESP]; Raetano, Carlos G. [UNESP]; Dal Pogetto, Mário H.F. Do A.; Costa, Saulo I. De A.; Christovam, Rafael De S. (My University, 2015)
Chemical control efficiency of Asian soybean rust (ASR), besides other factors, is associated with an appropriate fungicide application technique. This study aimed to evaluate the effect of different application technologies on spray deposition and ASR control in 2009-2010 and 2010-2011 crop seasons. The experimental design was a completely randomized block with four replications in a 3×2 factorial scheme. Three application rates were tested (60, 110 and 160 L ha-1) with and without silicone surfactant addition using a Brilliant Blue dye tracer in spray solution to analyze deposition (Experiment 1). For disease severity, thousand grain weight (TGW) and yield were evaluated on the same experimental design as used in Experiment 1 plus a control (3x2+1). It was used the fungicide mixture of azoxystrobin and epoxiconazol in four replications against ASR (Experiment 2). Application rates and surfactant use did not affect spray deposit levels on middle and bottom plant parts. The fungicide mixture at 160 L ha-1 was more effective for disease control and showed a greater yield in the 2010-2011 crop season. Chemical control with fungicides and application rates proper to the plant growing stage become essential to ensure a good soybean yield.
Effects of silicone surfactant and application rates on spray deposition and soybean rust control
Keywords: Adjuvants; Application technology; Spray deposition